Analisa Faktor-Faktor Sistem Informasi Akuntansi dan Kompetensi Sumber Daya Manusia Berpengaruh Terhadap Kualitas Laporan Keuangan (Studi Pada PT.Newera Rubberindo) - Ari Bramasto (Lembaga Penelitian Universitas Langlangbuana, 2019)
The research set forth in this jurnal aims to analyze the factors of accounting information systems and human resource competencies that can affect the quality of financial statements. This research was conducted at PT. Nusa Rubberindo. The population in this study is the accounting and financial staff at the PT. How to collect data by distributing questionnaires. The sampling technique uses a purposive sampling method and the sample with the results of 40 respondents. Multiple linear regression analysis is used as an analytical method to obtain the magnitude of the relations and contributions between the variables x and y. The classic assumption test is the first step in using statistical methods. Hypothesis testing utilizes the t test and f test with the SPSS 19.0 For Windows program process. The results of the research analysis show that accounting information system factors and competency factors have their respective influence on one side of the quality of the financial statements and together on the other.